Substitution with Alternative Anti-TNFα Therapy (SAVANT)—Outcomes of a Crohn's Disease Cohort Undergoing Substitution Therapy with Certolizumab. Issue 6 (June 2016) - Boktor, Moheb; Motlis, Andrew; Aravantagi, Avinash; Sheth, Ankur; Jordan, Paul; Morris, James; Manas, Kenneth; Hussain, Nazneen; Cvek, Urska; Trutschl, Marjan; Becker, Felix; Alexander, J. Steven
Abstract : Background: Biological therapy targeting tumor necrosis factor-alfa has revolutionized the treatment of Crohn's disease (CD). Our study retrospectively reviewed clinical outcomes of 60 patients administratively substituted from Infliximab or Adalimumab to Certolizumab. Maintenance of disease and failure rates after substitution of anti–tumor necrosis factor-alfa agents in CD patients were monitored over 1 year, and this is the first outcomes study of patients maintained on Infliximab or Adalimumab substituted to Certolizumab. Methods: A hospital pharmacy directive required all patients on biological therapy to be administratively substituted to Certolizumab therapy. This single-center retrospective analysis initially included 68 CD patients presenting at Louisiana State University Health Sciences Center-Shreveport. Clinical, endoscopic, and serologic data were compared at baseline and at 4 intervals over 1 year. Results: Of 60 enrolled CD patients, 45 (75%) successfully transitioned to Certolizumab and had stable disease at 1 year. Of the 15 (25%) patients who "failed" substitution at 1 year, 5 were returned to Adalimumab and 7 to Infliximab; 3 were maintained on steroids awaiting subsequent therapy. Importantly, when patients were segregated on the basis of initial disease control, it was found that 3 (12.5%) previously well-controlled patients failed therapy, whereas 12 (33.3%) who initially had active disease failed Certolizumab substitution. Conclusions: Our study found that 25% of CD patients substituted to Cimzia failed substitution, whereas 75% still exhibited a good clinical response with stable disease at 1 year. Our findings indicate that disease status and behavior at the time of biological substitution may predict therapeutic responsiveness. Abstract : Article first published online 22 April 2016.